The seven lost secrets of success : - Vitale, Joe (John Wiley & Sons, 2007)
The principles are sound and sensible and guaranteed to help any businessperson make more money. Since 99.9 percent of businesses don't use them, anyone putting the seven lost secrets to work will gain an unbelievable edge over the competition.